2019
DOI: 10.1097/mph.0000000000001468
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Determinants of Invasive Fungal Infections in Children With Solid and Hematologic Malignancies in a Nonallogeneic Stem Cell Transplantation Setting: A Narrative Review

Abstract: Invasive fungal infections (IFIs) are an important cause of morbidity and mortality in children with cancer. An overview of studies on the frequency and determinants of IFI in pediatric oncology patients in nonallogeneic stem cell transplantation settings is lacking. We performed a literature review in Pubmed and Embase, and included 13 prospective and 23 retrospective studies. The IFI frequency (proven/probable based on EORTC criteria) in nonallogeneic stem cell transplantation pediatric cancer patients range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 48 publications
4
24
1
Order By: Relevance
“…We found that children with ALL and AML had a similar frequency of experiencing at least one episode of IFI. This finding is contrary to the previous data in the literature suggesting that the frequency of IFI episodes in AML is higher than that in ALL [ 4 , 19 ]. The prevalence of IFI in ALL is reported to be between 4% and 35% depending on the era, chemotherapy protocol, risk categories, and antifungal prophylaxis [ 6 , 7 , 12 , 17 , 20 , 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We found that children with ALL and AML had a similar frequency of experiencing at least one episode of IFI. This finding is contrary to the previous data in the literature suggesting that the frequency of IFI episodes in AML is higher than that in ALL [ 4 , 19 ]. The prevalence of IFI in ALL is reported to be between 4% and 35% depending on the era, chemotherapy protocol, risk categories, and antifungal prophylaxis [ 6 , 7 , 12 , 17 , 20 , 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the incidence of IFI episodes was found to be 10.4%. The incidence in cases of hematologic malignancies ranged between 1.7% and 35.4% in various studies [ 4 , 9 , 10 , 11 , 12 ]. However, it may increase further in autopsy findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensified anticancer treatment is now increasingly used even in elderly patients; this is true even for the most aggressive diseases requiring very intensive treatment like allogeneic stem cell transplantation [ 74 ]. Intensified treatment will usually increase the risk of severe neutropenia and such severely immunocompromised patients are prone to a wide range of viral, bacterial, and fungal infections [ 117 , 118 , 119 , 120 , 121 , 122 ]. CRP levels can be used for the evaluation of anti-infectious treatment.…”
Section: Discussionmentioning
confidence: 99%